TI_GERICHTE 12.2015.208 vom 7. Februar 2017 , Disconoscimento di debito - riconoscimento di debito - mediazione o mandato - TI Tribunale d'appello (2017)
Disconoscimento di debito - riconoscimento di debito - mediazione o mandato